EFFECTS OF BIOFERTILIZER “M-STAR” ON LAND PRODUCTIVITY AND GROWTH OF SWEET CORN IN ACID SULPHATE SOIL OF SWAMPLAND - Mukhlis Mukhlis; Yuli Lestari (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2013)
This research aims to test the effectiveness of biofertilizer “M-Star” in increasing land productivity, growth of sweet corn and the efficiency of inorganic fertilizer used in acid sulphate soil of swampland. Research was conducted from May – July, 2012 in acid sulphate soil of Barambai, Barito Kuala Regency, South Kalimantan. The treatments involved (B1) Biofertilizer 25 kg/ha, (B2) Biofertilizer 15 kg/ha, (P1) NPK (recommendation dose), (P2) NPK (1/2 recommendation dose), (B1P1) Biofertilizer 25 kg/ha + NPK (recommended dose), (B1P2) Biofertilizer 25 kg/ha + NPK (1/2 recommended dose), (B2P1) Biofertilizer 15 kg/ha + NPK (recommended dose), (B2P2) Biofertilizer 15 kg/ha + NPK (1/2 recommended dose), and (K) No fertilizer. The treatments were arranged by randomized completely block design with 3 replications. Recommended dose of NPK fertilizer was at 90-60-50 NPK kg/ha. Observations were conducted on soil pH, soil and plant nutrients, growth of sweet corn (plant height and biomass weight), and microbial population. Research results showed that 15 kg/ha biofertilizer “M-Star” combined with inorganic NPK fertilizer could increase soil nutrients and sweet corn growth. This biofertilizer also increased the efficiency of inorganic fertilizer by 50%.Keywords: biofertilizer, sweet corn, swampland